Preventing child maltreatment : multicultural considerations in the United States - Fuentes, Milton A.; Deboard-Lucas, Renee; Singer, Rachel (Psychologist) (Violence against women and children, 2022)
"Preventing Child Maltreatment: Multicultural Considerations in the United States is the first book in a concentrated series that examines child maltreatment across minoritized, cultural groups. Specifically, this volume examines core multicultural concepts (e.g., intersectionality, acculturation, spirituality, oppression) as they relate to child maltreatment in the United States, while the other books take a closer look at particular ethnic or racial communities in this country. Additionally, this book examines child maltreatment through the intersection of feminist, multicultural, and prevention/wellness promotion lenses. Recommendations for treatment in each book build on a foundation of prevention and wellness promotion, along with multicultural and feminist theories. Throughout this book, five case studies, which are introduced in Chapter One, are revisited to help the readers make important and meaningful connections between theory and practice"--